2014
DOI: 10.2175/106143014x13896437493517
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Degradation of Nonylphenol (Endocrine Disruptor) by Using Ultraviolet Irradiation in the Presence of Hydrogen Peroxide

Abstract: The photodegradation of nonylphenol under UV irradiation was investigated in an aqueous solution containing hydrogen peroxide (H2O2) as the photochemically active substance was investigated. Influences of pH, the concentration of hydrogen peroxide, and the initial concentration of nonylphenol were studied. The following conditions were determined as optimal for nonylphenol removal: pH 1, H2O2 concentration of 40 mg/L, and an initial nonylphenol concentration of 15 of mg/L. Under these conditions, the removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…F rap decreased gradually, whereas F slow increased; meanwhile, k rap and k slow ranged from 0.11 to 1.28 and 0.0001 to 0.0082 day −1 , respectively (Table 2). Previous investigations showed that advanced oxidation technology rapidly degrades NP in various aqueous solutions within 10 h, suggesting higher degradation constants ranging from 34 to 1447 day −1 (Dulov et al., 2013; Kouakou et al., 2014). However, the complete degradation of NP required 10 and 20 days in aerobic soil and sediment/paddy soil, respectively, suggesting slow degradation constants ranging from 0.09 to 0.58 day −1 (Shan et al., 2011; Ying & Kookana, 2003, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…F rap decreased gradually, whereas F slow increased; meanwhile, k rap and k slow ranged from 0.11 to 1.28 and 0.0001 to 0.0082 day −1 , respectively (Table 2). Previous investigations showed that advanced oxidation technology rapidly degrades NP in various aqueous solutions within 10 h, suggesting higher degradation constants ranging from 34 to 1447 day −1 (Dulov et al., 2013; Kouakou et al., 2014). However, the complete degradation of NP required 10 and 20 days in aerobic soil and sediment/paddy soil, respectively, suggesting slow degradation constants ranging from 0.09 to 0.58 day −1 (Shan et al., 2011; Ying & Kookana, 2003, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Also concentrations of NP ranging from n.d. to 41.3µg/L were detected in Lake Shihwa in Korea [28] for freshwater. In comparison with those studies and EPA standards for freshwater [29], Fen and Shao rivers concentrations are higher so that they can be consider as polluted rivers considering these chemicals and industries in this city should apply some treatments or degradation processes before introducing their wastewater into environment in order to release non or less toxic products from degradation processes as Kouakou [30] found in their works. Table 3 shows almost neutral pH of groundwater samples which are ranged between 6.43 and 7.88.…”
Section: Surface Watermentioning
confidence: 93%